Effect of oxidative stress on cognitive functions in children with obesity - Özer, Samet; Bütün, İlknur; Bozkurt, Hasan (The European Research Journal, 2024)
Objectives: This study aims to evaluate the relationship between the oxidative stress induced by obesity and metabolic changes in the cognitive functions of obese children. Methods: Thirty-three obese children and adolescents (age: 8-18); and 33 healthy children similar in terms of age and gender were enrolled. Children were diagnosed with obesity according to the Turkish children's body mass index (BMI) curves. Patients over the 95th percentile in terms of Turkish children's BMI curves considering their genders and age were called obese children. Obese children were excluded whose obesity was related to any syndrome or disease. Neurocognitive functions including the Visual Memory Test, Finger Tapping Test, Memory Test, Symbol Digit Coding, Stroop Test, Continuous Performance Test, and Shifting Attention Test were evaluated with the battery tests of Central Nervous System Vital Signs (CNSVS) via computer. Malondialdehyde (MDA) and protein carbonyl (PC) were analyzed to determine the oxidative stress. After 10 hours overnight fast, blood samples were collected to determine Fasting glucose, total cholesterol, triglyceride, low-density lipoprotein, high-density lipoprotein, liver enzymes aspartate aminotransferase and alanine aminotransferase by using methods. Results: MDA and PC levels in obese children were founs significantly higher (0.78±0.16 µmol/L;198.30±84.45 nmol/mL) than the controls (0.5±0.10 µmol/L; 125.35±43.52 nmol/mL) (P